Contextual fear conditioning in virtual reality is affected by 5HTTLPR and NPSR1 polymorphisms: effects on fear-potentiated startle - Glotzbach-Schoon, Evelyn; Andreatta, Marta; Reif, Andreas; Ewald, Heike; Tröger, Christian; Baumann, Christian; Deckert, Jürgen; Mühlberger, Andreas; Pauli, Paul (Frontiers in Behavioral Neuroscience, 2013)
The serotonin (5-HT) and neuropeptide S (NPS) systems are discussed as important genetic modulators of fear and sustained anxiety contributing to the etiology of anxiety disorders. Sustained anxiety is a crucial characteristic of most anxiety disorders which likely develops through context conditioning. This study investigated if and how genetic alterations of the 5-HT and the NPS systems as well as their interaction modulate contextual fear conditioning; specifically, function polymorphic variants in the genes coding for the 5-HT transporter (5HTT) and the NPS receptor (NPSR1) were studied. A large group of healthy volunteers was therefore stratified for 5HTTLPR (S+ vs. LL carriers) and NPSR1 rs324981 (T+ vs. AA carriers) polymorphisms resulting in four genotype groups (S+/T+, S+/AA, LL/T+, LL/AA) of 20 participants each. All participants underwent contextual fear conditioning and extinction using a virtual reality paradigm. During acquisition, one virtual office room (anxiety context, CXT+) was paired with an unpredictable electric stimulus (unconditioned stimulus, US), whereas another virtual office room was not paired with any US (safety context, CXT-). During extinction no US was administered. Anxiety responses were quantified by fear-potentiated startle and ratings. Most importantly, we found a gene × gene interaction on fear-potentiated startle. Only carriers of both risk alleles (S+/T+) exhibited higher startle responses in CXT+ compared to CXT-. In contrast, anxiety ratings were only influenced by the NPSR1 polymorphism with AA carriers showing higher anxiety ratings in CXT+ as compared to CXT-. Our results speak in favor of a two level account of fear conditioning with diverging effects on implicit vs. explicit fear responses. Contextual fear reflected in potentiated startle responses may be an endophenotype for anxiety disorders.